(untitled) (Journal of Asian Development Studies, 2013)
Present study was conducted during 2010, in four Agricultural Universities of Pakistan, with the aim to investigate the perception of the faculty members in agriculture universities about the effectiveness of the existing agriculture extension curricula. For this sample size was determined by Fitzgibbon and Morris (1987) table and grand total of the sample reached to 32. Primary data was collected from the teachers of the concerned universities, through pre-tested structured mailed questionnaire. Data was analyzed using descriptive statistics and chi-square test. Main findings of the study revealed that 100% and 89% respondents either strongly agreed or agreed that the evaluation system of the agriculture extension curricula was based upon the items which tested knowledge and the items which tested comprehension and results the acceptance of null hypothesis. Also 92%, 85% and 81% respondents either strongly agreed or agreed that the students complete the course with a good understanding of agriculture extension program, services and have a good technical understanding of the subject matter respectively and alternative hypothesis was rejected. Moreover 84% and 77% respondents either strongly agreed or agreed that the curricula developed understanding of concepts and principles of the extension subject and improved communication skills. However, 23%, 38% respondents rated the curricula content and structure with respect to scope and topics as excellent and good. It was also found that 15%, 50% and 19% respondents rated the curricula content and structure with respect to technical merit as excellent, good and fair respectively. Major drawbacks in the curricula were less practical work and field involvement, not according to local needs and the problem of repetition/overlapping. The study recommends that curricula should be upgraded from present conditions, made it more practical oriented and practical nature according to the local needs.